Adhesive-free adhesion between polytetrafluoroethylene (PTFE) and isobutylene–isoprene rubber (IIR) via heat-assisted plasma treatment. Issue 11 (20th January 2017) - Ohkubo, Y.; Ishihara, K.; Sato, H.; Shibahara, M.; Nagatani, A.; Honda, K.; Endo, K.; Yamamura, Y.
Abstract : A polytetrafluoroethylene (PTFE) surface was modified using atmospheric pressure plasma treatment under heating (heat-assisted plasma treatment) to promote its direct adhesion to isobutylene–isoprene rubber (IIR) without any adhesives. Abstract : A polytetrafluoroethylene (PTFE) surface was modified using atmospheric pressure plasma treatment under heating (heat-assisted plasma treatment) to promote its direct adhesion to isobutylene–isoprene rubber (IIR) without any adhesives. Plasma-treated PTFE and unvulcanised IIR were thermally compressed and their adhesion strength was evaluated via a T-peel test. Heat-assisted plasma treatments conducted above 250 °C drastically increased the adhesion strength over 2.0 N mm −1 before IIR failure. The plasma-treated PTFE surface was evaluated using X-ray photoelectron spectroscopy, nanoindentation and scanning electron microscopy. The results of these analyses indicated that the adhesion strength drastically increased because heat-assisted plasma treatment promoted the formation of carbon–carbon crosslinks and/or etching of a weak boundary layer (WBL) on the PTFE surface. This led to the recovery of the WBL in PTFE, which resulted in the prevention of PTFE inter-layer peeling in the WBL. In addition, the estimated lifetime of the surface modification surprisingly exceeded one year.